2014
DOI: 10.1038/srep06160
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific mechanical and geometrical control of cell viability and actin cytoskeleton alignment

Abstract: Different tissues have specific mechanical properties and cells of different geometries, such as elongated muscle cells and polygonal endothelial cells, which are precisely regulated during embryo development. However, the mechanisms that underlie these processes are not clear. Here, we built an in vitro model to mimic the cellular microenvironment of muscle by combining both mechanical stretch and geometrical control. We found that mechanical stretch was a key factor that determined the optimal geometry of my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 44 publications
2
28
0
Order By: Relevance
“…The assembly of actin filaments into contractile stress fibers follows a mechanism common among adherent cell types (49), and actin stress fiber alignment is also seen in other cell types patterned into rectangular shapes (26,50,51). Nonmuscle actin stress fibers have several homologies with their myofibril isoforms in contractility, organization, and composition (49,52,53).…”
Section: Discussionmentioning
confidence: 99%
“…The assembly of actin filaments into contractile stress fibers follows a mechanism common among adherent cell types (49), and actin stress fiber alignment is also seen in other cell types patterned into rectangular shapes (26,50,51). Nonmuscle actin stress fibers have several homologies with their myofibril isoforms in contractility, organization, and composition (49,52,53).…”
Section: Discussionmentioning
confidence: 99%
“…[23] However, prior studies have focused predominantly on 2D patterns or the study of single cells in confined spaces, [11, 24, 25] and only recently have 3D patterned wells and surfaces started to be explored to investigate the collective behavior of cells. [26, 27] In our work, we utilized soft-lithographic techniques to address a fundamental question in cell biology: How does anisotropy alter the cell behavior of cell populations and their generated matrix in 3D anisotropic spaces?…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that cytoskeletal organization and nuclear morphology are regulated by extracellular mechanical signals, such as substrate stiffness and geometry (32)(33)(34)(35)(36)(37)(38)(39)(40)(41). With the cytoskeleton physically linked to the nucleoskeleton, these extracellular mechanical signals can therefore be used to mediate changes in chromatin structure.…”
mentioning
confidence: 99%